Slumdog millionaire - Boyle, Danny; Patel, Dev; Pinto, Freida; Kapoor, Anil; Khan, Irrfan ([place of publication not identified]: [publisher not identified], 2008)
The story of Jamal Malik, an 18 year-old orphan from the slums of Mumbai, who is about to experience the biggest day of his life. With the whole nation watching, he is just one question away from winning a staggering 20 million rupees on India's'Who Wants To Be A Millionaire?' But when the show breaks for the night, police arrest him on suspicion of cheating; how could a street kid know so much? Desperate to prove his innocence, Jamal tells the story of his life in the slum where he and his brother grew up, of their adventures together on the road, of vicious encounters with local gangs, and of Latika, the girl he loved and lost. Each chapter of his story reveals the key to the answer to one of the game show's questions. Intrigued by Jamal's story, the jaded Police Inspector begins to wonder what young man with no apparent desire for riches is really doing on this game show? When the new day dawns and Jamal returns to answer the final question, the Inspector and sixty million viewers are about to find out...
Based on the novel'Q & A' by Vikas Swarup.
Executive producer, Francois Ivernel, Cameron McCracken ; editor, Chris Dickens ; music producer, A.R. Rahman.
Dev Patel, Freida Pinto, Anil Kapoor, Irrfan Khan, Madhur Mittal, Saurabh Shukla.
LPF: PG13
DVD format, MPEG, NTSC, Stereo, Region 3, Dolby Digital.
In English and Hindi with optional English, Chinese and Malay subtitles.
Keywords: Orphans -- India -- Mumbai -- Drama; Television quiz shows -- India -- Mumbai -- Drama; Love in motion pictures